MOCVD of WSe2 crystals on highly crystalline single- and multi-layer CVD graphene. (15th January 2023) - Huet, Benjamin; Bachu, Saiphaneendra; Alem, Nasim; Snyder, David W.; Redwing, Joan M.
Abstract: The scalable synthesis of van der Waals vertical heterostructures (vdWHs) is viewed as an important milestone for the fabrication of novel 2D-based functional applications. Combining semi-metallic graphene with semiconducting transition metal dichalcogenides (TMDs) shows great potential to explore new device architectures with unique functionalities. In this work, we investigate the gas-source metal–organic chemical vapor deposition (MOCVD) of tungsten selenide (WSe2 ) on highly crystalline CVD graphene. Single- and multi-layer graphene constitute interesting testing grounds for investigating fundamental WSe2 growth mechanisms owing to its atomically smooth surface, absence of dangling bonds, chemical inertness, and hexagonal lattice symmetry. Our experimental results show how the graphene template properties influence the WSe2 nucleation site density, growth rate, in-plane orientation, and thickness. In particular, we found that WSe2 growth behavior strongly depends on the number of graphene layers, their stacking order/twisting angle, as well as on the nature of the substrate underneath. Graphical abstract: